MANAJEMEN STRES PADA PEMILIK USAHA KECIL MENENGAH (UKM) BIDANG KULINER DI KOTA KEDIRI - Gunawan, Frans Christian; Sahertian, Hallie J.; Broto, Felik S. W.W. (Akubis : Jurnal Akuntansi dan Bisnis, 2019)
Stress management is a common knowledge and should be appliedby each individual in order to reduce high stress levels due thedemands and pressures of works and personal life of eachindividual. Although not most of all, Stress Management can beimplemented by a business owner (SMEs) so that any activitywhich they do business to run well and thrive. In addition, StressManagement can be used to manage the activities of theorganization is currently running businesses, business owners canalso apply stress management on their personal lives in order tocreate a balance between business activities and their personallives. Causes of stress on business owners came from a variety ofsources which is derived from organizational factors andindividual factors that each individual has a different and its ownway of dealing with every obstacle that can possibly create stress.The purpose of this study was to determine the causes of stress onbusiness owners, especially in culinary’s bussines owners (Foodand Beverage) and how they perform is seen by the StressManagement Organizational and Individual aspects. The subjectsin this study is the Owner of Small and Medium Enterprises (SMEs)in Culinary derived from Kediri be a participant in this study. Theapproach used in this study is a qualitative case study approach.From the results of the study, researchers found that thephenomena that occur related to the causes of stress and stressmanagement is different for each individuals. The Stressors onOwner of Small and Medium Enterprises (SMEs) in Culinary areneed to known that the process of Stres Manajement can be donein order to maintain the continuity of their bussiness.